Community Perception and the Effectiveness of Bee Frequencies in Mitigating Human-Elephant Conflicts in Johor, Malaysia - Phoo, Qiao Lin; Mohamad Abdullah , Nazirah; Lok, Huey Kei; Koo Huang , Qing Yuan; Bakri , Nur A'alia Atierah; Khairunizan , Huda Khalidah (Enhanced Knowledge in Sciences and Technology, 2025)
Human-elephant conflict (HEC) poses significant challenges to both human livelihoods and elephant conservation, especially in regions where humans and elephants share the same habitat. Past studies have investigated traditional mitigation methods, such as fencing, which offer temporary relief but are unsustainable. This study was carried out in Kampung Lukut, Kota Tinggi, Johor, Malaysia, to assess community perceptions of HEC and evaluate the effectiveness of bee frequencies in deterring elephants. Two methods have been used throughout this study: questionnaire surveys with 200 villagers to acquire their experiences and opinions on HEC, and behavioural observations of elephants at the Johor Elephant Sanctuary (JES). The data revealed that all the participants considered HEC as a major problem for villagers because elephants often damage crops and property. Elephants were observed for their behavioural responses to bee frequencies, with playback sessions using recorded bee sounds at frequencies ranging from 200 Hz to 500 Hz and volumes between 10 and 60. The elephants’ reactions, such as moving away, were recorded to determine the deterrent effect. This method was found to be more effective than traditional approaches, such as electric fences or chemical repellents, which are often costly, harmful, and unsustainable. The findings suggest that bee frequencies are a promising alternative that offer a non-invasive, ethical, and long-term solution to HEC mitigation. Moreover, the study emphasizes the importance of community engagement and understanding public perceptions in developing effective conservation strategies. These results provide valuable insights for policymakers and conservationists, as they give a framework for balancing human needs with wildlife conservation and fostering coexistence between human and elephant.